2016
DOI: 10.3109/15513815.2016.1161684
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Meckel's Diverticulum: Report of 208 Cases and Review of the Literature

Abstract: We report a review of 208 cases of Meckel's diverticulum among pediatric patients from one single institution. One of the aims of this report is to highlight the different diagnostic modalities of Meckel's diverticulum since a majority of cases is undiagnosed prior to surgery. Our review shows 58 cases containing gastric and/or pancreatic heterotopic tissue, including two unique cases. The first case reported is a desmoid tumor arising at the tip of diverticulum, a case that, to our knowledge, has not been pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 8 publications
0
27
1
6
Order By: Relevance
“…Most patients with symptomatic or resected Meckel's are male. The largest retrospective patient series (each containing >100 patients) report a male to female gender ratio of 1.5:1 to 4:1 (see Table 3, [1218,20,21] ). The same is true for the database queries performed by Alemayehu et al [14] and Ruscher et al [16]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with symptomatic or resected Meckel's are male. The largest retrospective patient series (each containing >100 patients) report a male to female gender ratio of 1.5:1 to 4:1 (see Table 3, [1218,20,21] ). The same is true for the database queries performed by Alemayehu et al [14] and Ruscher et al [16]…”
Section: Resultsmentioning
confidence: 99%
“…Present in 4.6% to 71.0% of symptomatic Meckel's, gastric tissue is the most common, followed by pancreatic tissue present in 0% to 12.0%, see Table 5. [13,17,18,20,21,23,24,26,28,35,38,39,41] Articles are included in Table 5 if they differentiated between symptomatic and silent Meckel's and number of patients were >50.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported a 1.2–2% complication risk after MD resection compared with a lifetime morbidity risk 6.4–7% and recommended resection of all MDs encountered . The reported association of MD with intestinal cancer in adulthood impelled the tendency towards resection …”
Section: Discussionmentioning
confidence: 99%
“…5 According to Rho et al, the chief complaints were GI bleeding and nonspecific abdominal symptoms whereas some study mentions intestinal obstruction as the major presentation. [6][7][8] It is seen that bleeding and intussusception due to MD were more frequent in children under two years of age, whereas symptoms of intestinal obstruction occur more often after two years. 9 Rattan et al, mentioned intestinal obstruction (86%) was the most common presentation for MD.…”
Section: Discussionmentioning
confidence: 99%